Long-Term Functional Outcome after Internal Delorme's Procedure for Obstructed Defecation Syndrome, and the Role of Postoperative Rehabilitation. (4th May 2018) - Leo, C. A.; Campennì, P.; Hodgkinson, J. D.; Rossitti, P.; Digito, F.; De Carli, G.; D'Ambrosi, L.; Carducci, P.; Seriau, L.; Terrosu, G.
ABSTRACT: Purpose : To evaluate long-term functional outcomes of Internal Delorme's Procedure (IDP) in patients refractory to conservative treatment for Obstructed Defecation Syndrome (ODS), and to compare those who received postoperative rehabilitation with those who did not. Materials and methods : All patients with ODS refractory to nonoperative therapy were identified across three regional pelvic floor referral hospitals, and IDP was performed. Postoperatively selected patients received biofeedback therapy. Functional outcomes were established using the Cleveland Clinic Constipation (CCC) score and obstructed defecation score (OD score) preoperatively at 12 months and at the last available follow-up. Patient satisfaction was assessed with a visual analogue score. Results : From October 2006 to September 2013, IDP was performed in 170 patients: 77 received postoperative biofeedback and 93 did not. Mean follow-up was 6.3 years (range 1–8 years). CCC and OD scores improved significantly in both groups after 12 months and at the last follow-up ( p > 0.05). When comparing two groups while there was no significant difference between CCC and OD scores at 12 months, score was significantly better in the group that received rehabilitation at the last follow-up ( p = 0.001). Patient satisfaction was higher in the rehabilitation group (67%) compared with those without rehabilitation (55%). Clinical recurrence was recorded in nine patients who did not have postoperative rehabilitation. Conclusions : It has been demonstrated that IDP is associated with good long-term functional outcomes. Patients receiving rehabilitation had a better long-term follow-up, a higher overall satisfaction, and lower recurrence rate when compared with the patients who did not receive postoperative rehabilitation.